Red mud incorporated clay roof tiles as visible light‐active photocatalysts for building applications - Erdem Tevfik Özdemir; Ahmet Yavaş; Saadet Güler; Mustafa Erol (International Journal of Ceramic Engineering & Science, 2025)
Abstract This study aims to enhance the self‐cleaning properties of clay roof tiles by incorporating red mud as an industrial waste. This approach contributes to a sustainable environment by upcycling waste and developing an improved building material. Various analyses were conducted to compare the physical, structural, morphological, elemental, and optical properties of clay tiles with varying amounts of red mud. The characterization results indicated that the addition of red mud to clay roof tiles resulted in homogeneous and uniform tiles with enhanced physical properties. The red mud‐mixed clay roof tiles exhibited photocatalytic activity for the oxidation of methylene blue dye. Notably, while adding more than 5% red mud improved the physical properties, the optimal photocatalytic activity was observed in clay roof tiles with a 5% red mud addition. This study underscores the dual benefits of this approach: improving the functional properties of clay roof tiles and promoting the valorization of industrial waste.